Understanding immune–microbiota interactions in the intestine - Ahern, Philip P. (Immunology, 2019)
The past two decades have seen an explosion in research that aims to understand how the dynamic interplay with the gut microbiota impacts host health and disease, establishing a role for the gut microbiota in a plethora of pathologies. Understanding how health‐promoting microbiota are established and how beneficial host–microbiota interactions are maintained is of immense biomedical importance. Despite the enormous progress that has been made, our knowledge of the specific microbiota members that mediate these effects and the mechanisms underlying these interactions is rudimentary. The dearth of information regarding the nature of advantageous host–microbiota interactions, and the factors that cause these relationships to go awry, has hampered our ability to realize the therapeutic potential of the microbiota. Here we discuss key issues that limit current knowledge and describe a path forwards to improving our understanding of the contributions of the microbiota to host health.